Firm-level investment and monetary policy in Malaysia: do the interest rate and broad credit channels matter? - Abdul Karim, Zulkefly; Wan Ngah, Wan Azman Saini (Routledge, 2013)
This paper examines the effects of monetary policy on investment spending in Malaysia for 1990–2008 using firm-level data. The focal point of this paper is two main channels of monetary policy transmission mechanism, namely, the interest rate and broad credit channels. Using a dynamic neoclassical investment function, empirical results based on system generalised method of moments (GMM) estimations and a sample of 419 firms support the relevance of both interest rate and broad credit channels in influencing investment spending. The results also reveal that the effect of monetary policy channels on firm investment is heterogeneous, such that small firms (i.e. credit-constrained firms) are more responsive to monetary tightening when compared to large firms (i.e. less constrained firms).